2016
DOI: 10.1249/mss.0000000000001012
|View full text |Cite
|
Sign up to set email alerts
|

Altered Running Economy Directly Translates to Altered Distance-Running Performance

Abstract: Adding shoe mass predictably degrades running economy and slows 3000-m time-trial performance proportionally. Our data demonstrate that laboratory-based running economy measurements can accurately predict changes in distance-running race performance due to shoe modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
163
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(171 citation statements)
references
References 17 publications
5
163
2
1
Order By: Relevance
“…This 1% increase in E run is fairly consistent across a range of running speeds (Franz et al, 2012) and also degrades running performance (e.g., 3,000 m time-trial time) to a similar extent (Hoogkamer et al, 2016). It has been suggested that a potential mechanism by which footwear might reduce E run is because footwear serves to reduce some of the impact shock.…”
Section: Factors Not Affected By Trainingmentioning
confidence: 58%
“…This 1% increase in E run is fairly consistent across a range of running speeds (Franz et al, 2012) and also degrades running performance (e.g., 3,000 m time-trial time) to a similar extent (Hoogkamer et al, 2016). It has been suggested that a potential mechanism by which footwear might reduce E run is because footwear serves to reduce some of the impact shock.…”
Section: Factors Not Affected By Trainingmentioning
confidence: 58%
“…Using footwear that reduces athlete aerobic energy expenditure at a given running speed (improves their running economy) can augment distance-running performance by decreasing their relative aerobic intensity. 13 An established method of improving footwear to augment athlete distance-running performance is to reduce its mass. 1, 2, 4, 5 Based on literature values, if an aforementioned Olympic marathoner re-raced in shoes that were 100 g less than their original footwear, they would have expended aerobic energy at an ∼0.8% slower rate, 5 run the marathon ∼0.56% faster, 6 and taken the gold medal back to their home country.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of shoe weight (Franz et al 2012;Fuller et al 2015;Hoogkamer et al 2016), the increase of midsole material energy return (Frederick et al 1986;Worobets et al 2014;Sinclair et al 2016), and the increase of shoe 1 3 longitudinal bending stiffness (Roy and Stefanyshyn 2006) have been shown to improve the RE. These previous studies in the field of footwear have led Hoogkamer et al (2017b) to propose that the combination of weight saving, high midsole material energy return, and high longitudinal bending stiffness in a same pair of shoes was potentially beneficial to improve the RE.…”
Section: Introductionmentioning
confidence: 99%